PENERAPAN METODE DRILL DALAM PEMBELAJARAN AKUNTANSI JURNAL PENYESUAIAN - Suhendah, Rousilita; Lie, irene kim; widjaja, karen (Jurnal Bakti Masyarakat Indonesia, 2024)
Adjusting entries is the more hardly accounting materials. High school students need a high level of understanding mastering this material. Adjusting entries is related to preparing work balance sheets and financial reports. Therefore, the team carried out training activities regarding adjusting entries. This training can increase high school students' understanding of adjustment journal material, so high school students are  be able to apply this material to make financial reports. The team will provide training method on adjusted journal materials using the drill learning method. This drill learning method will divided into several stages. The first stage is giving a pretest, where high school students will get a pretest to see their initial understanding of adjusting journals. The next step is to provide teach on adjustment journal material, and ends with giving a posttest. The average pretest score was 44.54, and the posttest was 86.36. It means that the Adjustment Journal training using the Drill method shows that there is an increase in the understanding and abilities of the students participating in the training before and after learning to use the drill method. Accounting is  very difficul subject because this subject is a cycle that relates one material to another. It means that teaching strategies and methods are needed that are appropriate to the circumstances in providing accounting material to students. This activity focuses on applying the drill learning method and adjusting journal accounting to students. The drill method is a teaching method that involves conducting repeated exercises with intensive focus. ABSTRAK Jurnal penyesuaian adalah materi akuntansi yang tersulit. Siswa-siswi SMA memerlukan tingkat pemahaman yang tinggi dalam menguasai materi ini. Jurnal penyesuaian berkaitan dengan penyusunan neraca kerja dan laporan keuangan. Oleh karena itu, tim PKM melakukan kegiatan pelatihan mengenai jurnal penyesuaian. Pelatihan ini dapat memperluas  pengetahuan siswa SMA terhadap konten jurnal penyesuaian, sehingga siswa SMA mampu menerapkan materi tersebut untuk membuat laporan keuangan. Tim PKM akan memberikan pelatihan materi jurnal penyesuaian dengan metode pembelajaran drill. Metode pembelajaran drill ini akan dibagi menjadi beberapa tahap. Tahap pertama adalah pemberian pretest, dimana siswa SMA akan mendapatkan pretest untuk melihat pemahaman awal mengenai jurnal penyesuaian. Langkah selanjutnya adalah memberikan pengajaran materi jurnal penyesuaian, dan diakhiri dengan pemberian posttest. Rata-rata nilai pretest adalah 44,54 dan nilai posttest 86,36. Ini berarti metode kegiatan pengabdian kepada Masyarakat adalah berupa pelatihan untuk materi Jurnal Penyesuaian dengan metode Drill menunjukkan adanya peningkatan pemahaman dan kemampuan siswa yang mengikuti pelatihan sebelum dan sesudah pembelajaran menggunakan metode Drill. Akuntansi adalah topik  yang sangat sulit karena merupakan suatu siklus yang menghubungkan topik yang satu dengan topik yang lain. Artinya diperlukan strategi dan metode pengajaran yang sesuai dengan keadaan dalam memberikan materi akuntansi kepada siswa. Kegiatan ini fokus pada penerapan metode drill pada pembelajaran  akuntansi jurnal penyesuaian akuntansi jurnal kepada siswa. Metode drill adalah metode pengajaran yang melibatkan pelaksanaan latihan berulang-ulang dengan fokus yang intensif.